Corrosion of Reinforcing Steel in Fiber Reinforced Cementitious Composites - Mihashi, H.; Ahmed, Shaikh; Kobayakawa, A. (Japan Concrete Institute, 2011)
For the purpose of global sustainability the long life of structures is essential and the durability performance of reinforced concrete structures is one of the key issues to be resolved. This paper reports the results of a series of long term corrosion tests on fiber reinforced cementitious composites containing polyethylene (PE) alone and hybrid steel cord (SC) and PE fibers. The results are also compared with ordinary mortar. The specimens are subjected to accelerated corrosion for one year by applying external potential to the steel bar anode and a cathode made out of a steel wire mesh placed outside the concrete. Durability performances of the specimens are examined through regular monitoring of the time to initiate corrosion, the corrosion area ratio, corrosion depth, and the amount of steel loss. Results show that the hybrid fiber reinforced cementitious composites (HFRCC) containing hybrid SC and PE fibers exhibited excellent performance compared to mortar and fiber reinforced cementitious composites (FRCC) containing PE fiber. The order of the durability performance is HFRCC, FRCC, and Mortar. It is observed that the sacrificial corrosion of some of the SC fibers in the HFRCC specimen played an important role in the significant reduction of steel bar corrosion in the specimen.